Impact of lockdown due to COVID-19 on physical and mental health - Dr. Deepak Phalgune; Dr. Ajitkumar Mandlecha; Dr. Gous Mujawar (International Journal of Indian Psychȯlogy, 2022)
Background: The COVID-19 pandemic has brought into focus the mental health of various affected populations. Studies on the effects on mental health due to COVID-19 are scarce. The aim of the present study was to find the impact of lockdown due to COVID-19 on physical and mental health. Methods: This cross-sectional study was conducted between June and August 2020 in 310 individuals. An online questionnaire on the Google form platform, internally validated was sent through email and What’s App. The primary outcome measure was to assess the impact of lockdown on physical and mental health, whereas the secondary outcome measure was to study the impact of lockdown on individuals’ daily habits. A comparison of the distribution of categorical variables was done using Chi-square or Fisher’s exact test. Results: Mental health problems and stress were increased in 42.9 % and 61.0 % of respondents. In all 61.3 % and 58.4 % reported a positive change in attitude towards life and enjoyed their activities during lockdown respectively, whereas 11.9 % of respondents lost confidence in themselves. The majority of the respondents followed preventive measures such as the use of masks, hand wash and social distancing. A higher percentage of respondents reported a positive change in attitude towards life and enjoyed their activities during lockdown who practiced Yoga and exercised regularly. Conclusions: Almost half of the participants had mental health problems and stress during COVID-19 lockdown. Regular exercise and Yoga may be useful for a positive change in attitude.